Masked face recognition: Human versus machine - Naser Damer; Fadi Boutros; Marius Süßmilch; Meiling Fang; Florian Kirchbuchner; Arjan Kuijper (IET Biometrics)
Abstract The recent COVID‐19 pandemic has increased the focus on hygienic and contactless identity verification methods. However, the pandemic led to the wide use of face masks, essential to keep the pandemic under control. The effect of wearing a mask on face recognition (FR) in a collaborative environment is a currently sensitive yet understudied issue. Recent reports have tackled this by evaluating the masked probe effect on the performance of automatic FR solutions. However, such solutions can fail in certain processes, leading to the verification task being performed by a human expert. This work provides a joint evaluation and in‐depth analyses of the face verification performance of human experts in comparison to state‐of‐the‐art automatic FR solutions. This involves an extensive evaluation by human experts and 4 automatic recognition solutions. The study concludes with a set of take‐home messages on different aspects of the correlation between the verification behaviour of humans and machines.